The Role of the Village Government in Implementing the Family Hope Program (PKH) in Tinelo Village, Tilango District, Gorontalo Regency - Sasmitha Maharani Suharto; Jusrin Kadir; I Kadek Satria Arsana (Formosa Journal of Applied Sciences, 2023)
The aim of this research is so that the government's role in actualizing the PKH (Family Hope Program) program in the villages of Tinelo, Tilango, Gorontalo can be known during its implementation. With a research focus, namely coordination, data validation, and data distribution. The type of research used to discuss and process information in this research is descriptive qualitative. Meanwhile, the method used to collect information is by observation, interviews, and also literature review. The technique used to analyze data is qualitative analysis according to the type of research. The results obtained from the conclusion are that the role of the village government in implementing the Family Hope Program (PKH) has not been effective. This can be seen from the aspect that coordination has not been effective, data validity has not been effective, and aid distribution has not been effective in Tinelo Village, Tilango District, Gorontalo Regency.